Kesenjangan ekonomi di era digital : Bagaimana cara menyelesaikan kesenjangan digital pada negeri ini? - Muniroh, Tika Imro’atul (Maliki Interdisciplinary Journal, 2025)
The economic gap in the digital era poses an increasingly pressing challenge, despite technology offering various opportunities. This research aims to analyze the causes of the digital divide and its impact on society. Through a comprehensive approach, this study proposes enhancing access to education and relevant digital skills training, as well as developing equitable infrastructure across regions. The "Bridging the Digital Divide" project is designed to provide technology access and training for underserved individuals. Collaboration among government, private sector, and communities is crucial for creating an inclusive digital ecosystem. Research findings indicate that coordinated efforts to improve digital literacy and technology access can help foster a more just and prosperous society. With appropriate strategies, it is hoped that the digital divide can be minimized, allowing all segments of society to benefit from technological advancements. This study emphasizes the importance of involving various stakeholders in addressing the issue of the digital divide to achieve collective welfare.